2005
DOI: 10.1007/bf02344737
|View full text |Cite
|
Sign up to set email alerts
|

Implantable device for long-term electrical stimulation of denervated muscles in rabbits

Abstract: Although denervating injuries produce severe atrophic changes in mammalian skeletal muscle, a degree of functional restoration can be achieved through an intensive regime of electrical stimulation. An implantable stimulator was developed so that the long-term effects of different stimulation protocols could be compared in rabbits. The device, which is powered by two lithium thionyl chloride batteries, is small enough to be implanted in the peritoneal cavity. All stimulation parameters can be specified over a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…2 To achieve reliable direct muscle activation for periods up to 3 months, we used implanted programmable stimulators developed specifically for the project. 23 Stimulation was initiated 10 weeks after nerve section; by this time, muscle mass is about 40% of normal. 2 This experimental design reflects clinical reality: stimulation would not normally be initiated until some months post-injury, so the requirement is for a technique that will reverse established denervation atrophy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 To achieve reliable direct muscle activation for periods up to 3 months, we used implanted programmable stimulators developed specifically for the project. 23 Stimulation was initiated 10 weeks after nerve section; by this time, muscle mass is about 40% of normal. 2 This experimental design reflects clinical reality: stimulation would not normally be initiated until some months post-injury, so the requirement is for a technique that will reverse established denervation atrophy.…”
Section: Methodsmentioning
confidence: 99%
“…This selective motor denervation left sensation to the limb intact and avoided problems of selfmutilation. The implantable stimulator 23 was then introduced into the peritoneal cavity and anchored with sutures to the abdominal wall. The two leads and electrodes were conducted subcutaneously from the abdomen to the denervated hindlimb.…”
Section: Methodsmentioning
confidence: 99%
“…Implantable electrical stimulators (29) were inserted into the peritoneal cavity and secured in place. The wires and electrodes were routed subcutaneously from the abdomen to the left hindlimb.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of electrical stimulation on further myogenic differentiation has been analyzed in vitro www.intechopen.com (Donnelly et al, Stern-Straeter et al 2005) and in vivo (Fujita et al 2007). For clinical applications, devices for electrical stimulation have to be implantable and suitable for longterm stimulation (Jarvis & Salmons 2001, Lanmuller et al 2005. The in vivo experiments of Dennis and co-workers using implantable stimulation devices in the rat demonstrated that muscle mass as well as the maximum force of a denervated muscle can be maintained by electrical stimulation (Dennis et al 2003).…”
Section: Electrical Stimulation and Neurotizationmentioning
confidence: 99%